PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN LASIK CENTER SURABAYA DI SURABAYA EYE CLINIC - Dian Aprilia Puspitasari (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2021)
This research is to explain the influence of service quality on LASIK Center Surabaya patient satisfaction. This research is a quantitative study, a total of 65 people, data collection using a questionnaire that has been tested for validity and reliability while data analysis is done using multiple linear regression. The results of the study obtained based on the Validity Test showed that testing 6 variables for all statements on the questionnaire were valid. Reliability test of all variables obtained by Cronbach alpha value> 0.70 was declared reliable and for the Hypothesis Test based on the t-test there was a significant influence of Tangibles (tangible) on patient satisfaction as indicated by the t-test results of 4.925 with a significance level of 0,000. Significantly influence there is an influence of reliability (reliability) on patient satisfaction shown from the results of the t-test of 3.548 with a significance level of 0.001. Significantly there is an influence of Assurance (Guarantee) on patient satisfaction with a t count of 2.270 and a significance level of 0.027. Significantly there is an influence of Responsiveness (responsiveness) on patient satisfaction as indicated by the results of the t-test of 2.189 with a significance level of 0.033. Significantly there is an influence of Empathy (Empathy) on patient satisfaction with a t count of 2.103 and a significance level of 0.040.